A Literature Review about One of the Successful Skills of the 21st Century: Collaborative Ability Student - Astiswijaya, Nike; Kusnandi, Kusnandi; Juandi, Dadang (Didaktika Religia, 2023)
One of the important abilities for students to have and develop is the ability to collaborate. Although interest in collaboration as a skill required by students is increasing, the context of collaboration itself is still unclear. The purpose of this literature observation is to explore conceptualizations, definitions, and understandings in research literature related to collaboration. Collaboration is when in a group there is interaction between members, working together to provide the best role and working together to solve problems or achieve goals. To achieve this goal, there needs to be shared responsibility. The indicators most frequently used are the indicators mentioned by Trilling and Fadel, namely Cooperation, Flexibility, Responsibility, Compromise and Communication. Educators should pay attention to how the design of assessment tasks encourages all students in a group to participate, share thoughts, gather resources and ideas, manage assignments, manage time, and communicate effectively.